Effect of Vermicompost Dose to K Content in Leaves and Growth of Corn (Zea mays, L) on Ultisol - Nunung Nurjanah; Riwandi Riwandi; Hasanudin Hasanudin (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2020)
The objectives of this research were to obtain an optimum dose of vermicompost fertilizer to the nutrient levels of K in the leaves, K uptake, and corn growth in ultisols. This research were held in September until November 2018, which has been implemented in green house and the Laboratory of Soil Science, Faculty of Agriculture, University of Bengkulu. The research used Completely Randomized Design (CRD) with a single factor consisting of 7 levels of treatment and three replicates i.e. 0 , 2.5 , 5.0 , 7.5 , 10.0, 12.5, and 15.0 ton ha-1. The results showed that the optimum dose of vermicompost fertilizer 5.71 ton ha-1, resulting in leave K content of 0.59%, 9.5 ton vermicompost ha-1, producing the absorption of K leaves 31 kg ha-1, 9.59 ton vermicompost ha-1, producing a plant height 160.7 cm, 10.2 ton vermicompost ha-1, producing the fresh stover weight 27,561.2 kg ha-1, 98.9 ton vermicompost ha-1, producing the dry stover weight 5,675.5 kg ha-1, and 9.5 tons vermicompost ha-1, producing root dry weight 1,156 kg ha-1.